2018
DOI: 10.1016/j.ijrobp.2017.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CD4 Count on Treatment Toxicity and Tumor Recurrence in Human Immunodeficiency Virus–Positive Patients With Anal Cancer

Abstract: Lower pretreatment CD4 counts were associated with acute hematologic toxicity, and lower posttreatment CD4 count levels were associated with an increased risk of tumor recurrence. These results suggest that immune surveillance may play an important role in long-term disease control in anal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Demonstration of worse FFLR in HIV‐positive patients with low CD4 counts after treatment is not without precedence. A recent database analysis of 142 HIV‐positive patients found that post‐treatment CD4 count, and not pretreatment, was associated with a 54% increased risk of recurrence for every 100 cells per mm 3 decrease . Similarly, the current study found that post‐treatment CD4 count less than 150 cells per mm 3 resulted in a significantly worse OS among HIV‐positive patients ( p = .015), whereas pretreatment CD4 count was not significantly associated.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Demonstration of worse FFLR in HIV‐positive patients with low CD4 counts after treatment is not without precedence. A recent database analysis of 142 HIV‐positive patients found that post‐treatment CD4 count, and not pretreatment, was associated with a 54% increased risk of recurrence for every 100 cells per mm 3 decrease . Similarly, the current study found that post‐treatment CD4 count less than 150 cells per mm 3 resulted in a significantly worse OS among HIV‐positive patients ( p = .015), whereas pretreatment CD4 count was not significantly associated.…”
Section: Discussionsupporting
confidence: 58%
“…Even with these demographic differences, HIV‐positive patients were found to have similar T and N stage as HIV‐negative patients, with the majority having early stage disease. Regardless of the similarity of the baseline characteristics, multiple prior investigations have recognized worse FFLR and OS for HIV‐positive patients treated definitively for ASCC . In this series, HIV‐positive patients tended to have a FFLR more similar to HIV‐negative patients with one higher T‐stage (i.e., FFLR for HIV‐positive/T1 being similar to HIV‐negative/T2).…”
Section: Discussionmentioning
confidence: 70%
“…[19] In patients with HIV, insufficiency of glutathione (GSH) could lead to the depletion of radioprotective thiols and increased oxidative stress. A study by Alex et al [20] reported that HIV patients who are affected via anal cancer and have a CD4 test outcome of fewer than 200 have increased mucositis and bleeding and decreased tolerance suggesting a high requirement for lower remedy doses. [20]…”
Section: Methodsmentioning
confidence: 99%
“…A study by Alex et al [20] reported that HIV patients who are affected via anal cancer and have a CD4 test outcome of fewer than 200 have increased mucositis and bleeding and decreased tolerance suggesting a high requirement for lower remedy doses. [20]…”
Section: Methodsmentioning
confidence: 99%
“…In malignant diseases, tumour-infiltrating T cells have been associated with prognosis in malignant melanoma [111] and ovarian cancer [112]. In HIV-positive patients with anal cancer, lower CD4+ T cell counts were associated with worse treatment outcome [113]. Similar to CD4+ T cells several reports associate CD8+ T cells with improved survival in different forms of cancer [114,115,116].…”
Section: Project I: Identification Of Shared Disease Genesmentioning
confidence: 99%